Alleviation of allergic conjunctivitis by (±)5(6)-dihydroxy-8Z,11Z,14Z,17Z-eicosatetraenoic acid in mice - Nagata, Nanae; Suzuki, Tomoka; Takenouchi, Shinya; Kobayashi, Koji; Murata, Takahisa (Frontiers in Pharmacology, 2023)
Allergic conjunctivitis (AC) is a common ophthalmologic disorder that causes symptoms that often reduces a patient's quality of life (QOL). We investigated the effects of the eicosatetraenoic acid metabolite (±)5(6)-dihydroxy-8Z,11Z,14Z,17Z-eicosatetraenoic acid ((±)5(6)-DiHETE) on AC using a mouse model. Repeated topical application of ragweed pollen induced conjunctivitis, accompanied by eyelid edema and tearing in mice. Pollen application typically degranulates mast cells and recruits eosinophils to the conjunctiva. Intraperitoneal administration of 300 μg/kg of (±)5(6)-DiHETE significantly inhibited pollen-induced symptoms. The administration of (±)5(6)-DiHETE also attenuated mast cell degranulation and eosinophil infiltration into the conjunctiva. To assess the effects of (±)5(6)-DiHETE on the downstream pathway of mast cell activation in AC, we used a histamine-induced ocular inflammation model. Topical application of 4 μg/eye histamine caused eyelid edema and tearing and increased vascular permeability, as indicated by Evans blue dye extravasation. Intraperitoneal administration of 300 μg/kg or topical administration of 1 μg/eye (±)5( 6)-DiHETE inhibited histamine-induced manifestations. Finally, we assessed the effects of (±)5( 6)-DiHETE on itching. An intradermal injection of 10 μg serotonin in the cheek caused scratching behavior in mice. Intraperitoneal administration of 300 μg/kg (±)5(6)-DiHETE significantly inhibited serotonin-induced scratching. Thus, (±)5( 6)-DiHETE treatment broadly suppressed AC pathology and could be a novel treatment option for AC.